Analisis Penyelesaian Soal Cerita Matematika Berdasarkan Prosedur Newman Ditinjau dari Gaya Kognitif Siswa - Aprilia Afwika; Nida Jarmita; Zikra Hayati (Pencerah, 2023)
Most students were unable to solve math problems when the questions were changed to word problems, students could not understand nor were they able to solve math word problems. This study aims to describe students' errors based on Newman's procedure in solving word problems in terms of cognitive style and describe the causes of their errors. The type of research used is descriptive qualitative approach with data collection techniques written tests and interviews. The results of the study showed high cognitive students made mistakes on process skills, moderate cognitive students also made mistakes on process skills and low cognitive students made mistakes on the stages of reading questions, question transformation and process skills. The causes of errors made by students based on the Newman procedure are, students do not understand the questions well, students are confused about the steps for working on the questions, students are in a hurry to work on the questions, are not thorough in working on the questions, lack of mastery of the material, are not used to writing or using units and students are not used to working on math word problems. The five mistakes’ students made when working on math word problems were errors in reading the questions, errors in understanding the questions, errors in transforming the questions, errors in processing skills and errors in writing answers